Венозная система грудных конечностей лося (Alces alces L.) и ее клапанный аппарат. Сообщение II. Венозная система области предплечья, плеча и лопатки - Комаров, А.В. (Вестник зоологии, 1971)
By mean s of anatomi c methods the venous system is studied in 10 thoracic limbs
of foetuses and adult elks. The venous system of a thoracic limb ha s two lines: superficial and deep. The vessels of the superficial line are established to have the greatest
diameter of veins in antebrachial region and the vessels of deep line — in brachial region. The valves in veins in the antebrachial region are more frequent in the vessels of
deep line, and in brachial region — in superficial one. In foetuses at the age of 5.5 months the venous lumen is mainly formed and in line veins of the limb there is 62% of total amount of valves in adult animal.